Headmaster’s Leadership in Solving Problems at Islamic Elementary School (SDI) Hikmatul Fadhillah Medan - Rahmi, Sri (Jurnal Pendidikan Islam, 2018)
The school headmaster is at the forefront in cooperating to build human relations at school as well as its surrounding environment. Harmonious relations should be planned and implemented by the school headmaster as the top leader. The school headmaster is a leader, and a teacher is a colleague and a friend at work. In school management, headmaster-teacher relation is a mutual relation in making efforts to achieve a better quality of school management. This article uses a naturalistic phenomenological approach by studying events in certain situations. The article discusses leadership management of the school’s headmaster who used the human relation approach in solving problems. The headmaster also analyses some important problem-solving methods at the school by using a guided method towards human relation values, religions, personality, cross-check of facts, friendship, and polite conversation with lean voice.